Pengaruh Iklim Organisasi terhadap Kinerja Guru Madrasah Aliyah Negeri 13 Jakarta - Januar Barkah; Fahmi Hidayat (JUDICIOUS, 2021)
The purpose of this study was to determine how far the influence of organizational climate on teacher performance at Madrasah Aliyah Negeri 13 Jakarta. The research method used is descriptive quantitative, which is a form of research based on data collected during systematic research on the facts and properties of the object under study by combining the relationships between the variables involved, then interpreted based on theories and literature. literature that relates organizational climate to teacher performance. . The results of the t-test in the regression table are obtained, where the tcount obtained is 4,174 while the ttable for N = 62 is 2,001. So tcount is greater than ttable or 4.174 > 2.001. Because the hypothesis is formulated if tcount > ttable then H0 is rejected and Ha is accepted, and this result is proven that tcount > ttable means that there is indeed a positive and significant influence between Organizational Climate (Variable X2) on Teacher Performance (Variable Y). Based on the coefficient of determination test, 22.5% Organizational Climate has a positive effect on Teacher Performance while the remaining 77.5% is influenced by other factors outside the title of the study.